Uncertain Safety Allocating Responsibilities for Safety - Wetenschappelijke Raad voor het Regeringsbele (WRR, 2009)
Flood prevention, food safety, transport of hazardous materials, infectious diseases, the risks posed by new technologies, and many other threats to public health and the environment call for ongoing public alertness. However, the ways in which these safety risks are currently assessed and managed fall short of addressing the uncertainties of future threats. The contributors to this essential volume argue that in order to ensure future-proof safety policies, we should be adopting a new paradigm, one based on the precautionary principle: i.e. the notion that the vulnerability of humans, society and the natural environment requires a proactive approach to uncertainties. In this vital report, the Netherlands Scientific Council for Government Policy outlines ways to embody this principle in both private and public law and in various institutional arrangements.